Efecto de la suplementación alimenticia moderada en la producción lechera, concentración de sólidos totales y condición corporal en vacas lecheras en pastoreo - Balarezo Urresta, Luis Rodrigo (Tierra Infinita, 2015)
This research"™s objective was to evaluate the effect of feeding a moderate amount of supplement (a palm oil kernel meal and barley blend), on productive performance, milk production, total milk solids concentration and body condition score of dairy cows in an intensive grazing system when fed high quality grass. 32 cows randomly assigned to two treatments were used: P = grazing, and P + S6 = grazing plus 6 kg of supplement. The cows had unrestricted access to water and high quality pasture composed of rye grasses (Lolium perenne), cocksfoot (Dactylus glomerata), and clover (Trifolium repens L.). P + S6 Cows received 6 kg as fed supplement blend divided into two equal portions at milking times (4,7 kg Dry matter per day). Live weight and body condition were recorded biweekly. Milk production and composition were recorded and analyzed weekly. The supplementation did not modify milk volume per day, nor total milk solids concentrations. Milk protein and lactose were significantly modified (p=0,95). Body condition and live weight were not modified.